Test of fast neutron detectors for spectroscopy with (3He,n) two proton stripping reactions - Elbasher, Mohamed Elbasher Ahmed (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.